2021
DOI: 10.4103/ajm.ajm_113_20
|View full text |Cite
|
Sign up to set email alerts
|

Blood donation among university students: Practices, motivations, and barriers in Saudi Arabia

Abstract: Context: Blood transfusion is an essential medical procedure conducted with various purposes to provide patients with blood needed. The procedure saves patients’ lives, as blood cannot be manufactured artificially and can only be obtained from human blood sources. Aims: To assess the awareness of, perceptions of, motivations regarding, and barriers to blood donation among a sample of Jazan University students in the Kingdom of Saudi Arabia (KSA). Settings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“… 35 This might be due to the difference in the implementation of blood donation campaigns and different barriers to blood donation including being unqualified for blood donation and fear of contracting diseases. 36 …”
Section: Discussionmentioning
confidence: 99%
“… 35 This might be due to the difference in the implementation of blood donation campaigns and different barriers to blood donation including being unqualified for blood donation and fear of contracting diseases. 36 …”
Section: Discussionmentioning
confidence: 99%
“…The data collection tool was pretested on 5% (19) of the sample size on students in Gimbi campus which was out of the study setting. Besides, two-day training was given to data collectors and supervisors.…”
Section: Data Quality Controlmentioning
confidence: 99%
“…The previously conducted studies in different parts showed that the magnitude of blood donation practice range from 10% to 35.69% in Asia 14–16 and 10.64% to 61.69% in Africa 11 , 17 , 18 which was relatively incomparable with high-income countries. It was found to be 29% in Saudi Arabia, 19 26.7% in India, 20 27.1% in Ghana, 21 15.3% in Nigeria 22 and 22.6%–47.8%, 5 23–28 in different regions of Ethiopia. On top of this, various factors are identified as the factors that hinder blood donation practice.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations